Dampak Transformasi Sektor Kesehatan Di Indonesia Pasca Disahkan Undang-Undang Tentang Kesehatan No. 17 Tahun 2023 - Aurelia, Ara Maritza Madjida; Prasetyo, Teguh; Efrila, Efrila (Jurnal sosial dan sains, 2025)
This article aims to examine the impact of the transformation of the healthcare sector in Indonesia after the enactment of the Health Act No. 17 of 2023. The research methodology used in this study is a comprehensive literature review and analysis of relevant data. The findings of this research indicate that the transformation of the healthcare sector in Indonesia has resulted in significant changes in various aspects. These changes include improved access to healthcare services, enhanced quality of care, increased investment in healthcare infrastructure, and better healthcare governance. Additionally, the transformation has also led to the development of a more patient-centered approach in healthcare delivery. However, challenges such as inadequate funding, scarcity of healthcare professionals, and disparities in healthcare access between urban and rural areas still exist. In conclusion, the transformation of the healthcare sector in Indonesia has had both positive and negative impacts, and continuous efforts and reforms are needed to address the remaining challenges.